Radiative impact of improved global parameterisations of oceanic dry deposition of ozone and lightning-generated NOx - A. K. Luhar; I. E. Galbally; M. T. Woodhouse (Atmospheric Chemistry and Physics, 2022)
We investigated the radiative impact of recent process-based improvements to oceanic ozone (O3) dry deposition parameterisation and empirical improvements to lightning-generated oxides of nitrogen (LNOx) parameterisation by conducting a 5-year simulation of the Australian Community Climate and Earth System Simulator – United Kingdom Chemistry and Aerosol (ACCESS-UKCA) global chemistry–climate model, with radiative effects of O3, methane (CH4) and aerosol included. Compared to the base parameterisations, the global consequences of the two improved parameterisations on atmospheric composition are dominated by the LNOx change (which increases the LNOx production from 4.8 to 6.9 Tg N yr−1) and include (a) an increase in the O3 column of 3.75 DU, and this O3 change is centred on the tropical upper troposphere where O3 is most effective as a radiative forcer; (b) a decrease of 0.64 years in the atmospheric lifetime of CH4 due to an increase in hydroxyl radical, which corresponds to a decrease of 0.31 years in the CH4 lifetime per Tg N yr−1 change in LNOx; (c) an increase of 6.7 % in the column integrated condensation nuclei concentration; and (d) a slight increase in high-level cloud cover. The two combined parameterisation changes cause an increase of 86.3 mW m−2 in the globally-averaged all-sky net downward top-of-atmosphere (TOA) radiative flux (which is akin to instantaneous radiative forcing), and only 5 % of which is due to the dry deposition parameterisation change. Other global radiative changes from the use of the two parameterisations together include an increase in the downward longwave radiation and a decrease in the downward shortwave radiation at the earth's surface. The indirect effect of LNOx on aerosol and cloud cover can at least partly explain the differences in the downward shortwave flux at the surface. It is demonstrated that although the total global LNOx production may be the same, how LNOx is distributed spatially makes a difference to radiative transfer. We estimate that for a reported uncertainty range of 5±3 Tg N yr−1 in global estimates of LNOx, the uncertainty in the net downward TOA radiation is ±119 mW m−2. The corresponding uncertainly in the atmospheric methane lifetime is ±0.92 years. Thus, the value of LNOx used within a model will influence the effective radiative forcing (ERF) and global warming potential (GWP) of anthropogenic CH4, and influence the results of climate scenario modelling.